Human fetal to adult hemoglobin switching: changes in chromatin structure of the beta-globin gene locus. - Groudine, M (1983)
We have investigated the chromatin structure of the chromosomal DNA regions containing the human G gamma-, A gamma-, delta-, and beta-globin structural genes in both fetal and adult erythropoietic tissues and in two human erythroleukemia cells lines before and after induction. Our results indicate that DNase I introduces specific cuts into the beta-globin gene cluster in erythroid cells but not in leukocytes. The predominant sites are located at the 5' sides of the G gamma-, A gamma-, delta-, and beta-globin genes, within 200 base pairs of the respective cap sites. Examination of fetal liver cells has revealed the presence of hypersensitive sites at the 5' side of all four genes, whereas analysis of adult bone marrow has revealed the characteristic sites near the delta- and beta-globin genes but no hypersensitive sites at the 5' termini of the G gamma- or A gamma-globin genes. The presence of delta and beta hypersensitive sites in fetal cells suggests that the increment in expression of the delta and beta genes during development most likely involves the modulation of another pathway to gene expression. Using isolated nuclei from HEL and K562 cells, we have found that the G gamma, A gamma, delta, and beta genes are preferentially sensitive [relative to the pro-alpha2(I) collagen gene] to mild digestion with DNase I, whereas these genes are as resistant as collagen genes in cells that do not express globin. These findings are discussed within the context of chromatin structural correlates of hemoglobin switching.